THE ALBANIAN CUSTOM’S RIGHT IN HISTORICALJURIDICIAL ASPECT, A NOTE ABOUT LEKE DUKAGJINI AND SKANDERBEG’S CODE - Bevapi, Kujtim (European Scientific Journal, ESJ, 2012)
The article aims at treating what the Albanian custom’s right is, the historical and social conditions of its birth and its implementation. As well, it stops on the historical evolution of this right and on the considerations of some foreign and Albanian authors about it. The analysis is focused only on the codes of Leke Dukagjini and that of Scanderbeg, as two of the most important ones which acted in the north of the country, in Dukagjins’ and Kastriots’ principates. Their content and their composition as well as their basic features are described in the article. Special attention is dedicated to the originality of the Albanian custom’s right, considering these codes as moral codes, ethical and juridical codes with its institution, such as: the institute of Oath, hospitality, etc.